2010
DOI: 10.1172/jci40253
|View full text |Cite
|
Sign up to set email alerts
|

A retinoic acid–dependent network in the foregut controls formation of the mouse lung primordium

Abstract: The developmental abnormalities associated with disruption of signaling by retinoic acid (RA), the biologically active form of vitamin A, have been known for decades from studies in animal models and humans. These include defects in the respiratory system, such as lung hypoplasia and agenesis. However, the molecular events controlled by RA that lead to formation of the lung primordium from the primitive foregut remain unclear. Here, we present evidence that endogenous RA acts as a major regulatory signal integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 44 publications
(53 reference statements)
6
109
2
1
Order By: Relevance
“…However, a detailed epidemiologic study has not been performed and most of these countries lack registries of birth defects. In addition, it is well known that vitamin A and its metabolite retinoic acid have a crucial role in animal lung development (Chen et al, 2010), which is disturbed in patients with CDH. Further, maternal vitamin A repletion in a vitamin A deficient population improves lung function in the offspring (Checkley et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, a detailed epidemiologic study has not been performed and most of these countries lack registries of birth defects. In addition, it is well known that vitamin A and its metabolite retinoic acid have a crucial role in animal lung development (Chen et al, 2010), which is disturbed in patients with CDH. Further, maternal vitamin A repletion in a vitamin A deficient population improves lung function in the offspring (Checkley et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling has also been implicated in proximal-distal epithelial patterning and differentiation during lung development and the roles of other Wnt ligands remain obscure (Shu et al, 2005;Zhang et al, 2008). Interestingly, Wnt signaling is also absolutely required for the initial specification of the respiratory epithelial lineage from the foregut endoderm (Goss et al, 2009;Harris-Johnson et al, 2009;Chen et al, 2010).…”
Section: Epithelial Progenitor Regulationmentioning
confidence: 99%
“…Previous studies have shown that epithelial signaling molecules, including sonic hedgehog and vascular endothelial growth factors (VEGFs), regulate the proliferation and differentiation of mesenchymal cells (Healy et al, 2000;Miller et al, 2004;Del Moral et al, 2006;White et al, 2006;Chen et al, 2010). However, recent studies regarding the role of epithelial Wnts in vasculature development generate inconsistent conclusions (Shu et al, 2002;Rajagopal et al, 2008).…”
Section: Introductionmentioning
confidence: 99%